2012
DOI: 10.1097/psy.0b013e318240a7d8
|View full text |Cite
|
Sign up to set email alerts
|

Early Trauma and Inflammation

Abstract: Objective Although early trauma (trauma in childhood) has been linked to adult inflammation and adult disease of inflammatory origin, it remains unknown whether this relationship is due to long-term consequences of early life stress or other familial factors. Methods We examined 482 male middle aged twins (241 pairs) born between 1946 and 1956 from the Vietnam Era Twin Registry. Childhood traumatic experiences, before age 18, were measured retrospectively with the Early Trauma Inventory (ETI) and included ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…CRH, in turn, has been shown to have a pro-inflammatory effect in the periphery (85, 86), and increased levels of p CRH have been associated with intra-amniotic infection (72, 87). Moreover, previous studies of non-pregnant CT+ women have reported they exhibit an increased inflammatory status (88–90). Thus, the maternal environment also may modulate p CRH production via changes in the inflammatory milieu.…”
Section: Discussionmentioning
confidence: 93%
“…CRH, in turn, has been shown to have a pro-inflammatory effect in the periphery (85, 86), and increased levels of p CRH have been associated with intra-amniotic infection (72, 87). Moreover, previous studies of non-pregnant CT+ women have reported they exhibit an increased inflammatory status (88–90). Thus, the maternal environment also may modulate p CRH production via changes in the inflammatory milieu.…”
Section: Discussionmentioning
confidence: 93%
“…Other investigations of the biological link between early life stress and PTSD have implicated irregularities in inflammatory response and highlighted some novel biochemical and molecular markers that may prove useful for quantifying PTSD risk. Studies have shown shorter lengths of telomeres (the regions of repetitive nucleotide sequences located at the end of chromosomes) with early life stress history (Tyrka et al 2010; Shalev et al 2013) and with PTSD (O'Donovan et al 2011; Ladwig et al 2013; Zhang et al 2013); increased global DNA methylation with PTSD (Smith et al 2011); increased glucocorticoid receptor gene (NR3C1) methylation with CSA history (Perroud et al 2011); increased pathway activity of NF-ÎșB (a protein complex that controls expression of genes that code for inflammatory cytokines) in individuals with childhood-abuse related PTSD (Pace et al 2012); as well as higher C-reactive protein (CRP) and Interleukin-6 (IL-6) levels in individuals with a history of early life stress (Rooks et al 2012). However, since most studies of biological pathways have been cross-sectional, the chronology of early life stress, PTSD and biological changes remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been reported previously that both CRP and IL-6 levels are similar in twins, a finding that will emerge when the influence of adiposity is not taken into account, nor statistically considered as a contributing factor (Rooks et al, 2012; Wörns et al, 2006). In addition, there is a substantial literature reporting that allele polymorphisms affect IL-6 release, but that effect is most apparent in the context of inflammatory disorders, or when cells are activated in vitro by a proinflammatory stimulant (Bennermo et al, 2004; Brull et al, 2001; Burzotta et al, 2001; Shah et al, 2013).…”
Section: Discussionmentioning
confidence: 97%